Majas dalam Lirik Lagu Vinushka Oleh Dir En Grey - Raditya, Maulana Hasanudin; Damayanti, Silvia (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 2 (2022)DO - 10.24843/JS.2022.v04.i02.p07, 2022)
The research entitled "Majas in Vinushka Song Lyrics by Dir En Grey" aims to determine the form and function of figurative language contained in song lyrics. The data used in this study are the lyrics of the song Dir En Gray entitled Vinushka. The data was analyzed by using qualitative descriptive method. The theory used is the stylistic theory proposed by Keraf (2006), the theory of figurative language proposed by Tarrigan (2009) and the theory of the function of figurative language. The results shows that there are 2 types of figurative expressions in the lyrics of the Vinushka song, namely metaphorical and personification. The function of the figurative expressions in the song was expalaining, strengthening ideas, and bringing life to inanimate objects.